Analisis Peran Hands on Activity dalam Model Predict Observe Discuss Explain Terhadap Pemahaman Konsep Sains SD - Fiky Herdianto*; Hartono Hartono; Ali Sunarso (Universitas Syiah Kuala, 2022)
Learning science by rote can lead to misunderstandings or misconceptions. Misunderstanding of concept understanding must be avoided by students, so that the knowledge process in obtaining conceptual information is meaningful for students. This study aims to determine the role of the PODE Hands on Activity model in understanding science concepts for fourth grade elementary school students. This research uses a quantitative approach with a quasi experimental design type of research in the form of nonequivalent control group design. The sample of this study amounted to 60 fourth grade students of SD 1 Gulang and SD 1 Payaman. Data collection techniques are multiple choice and hands on activity observation sheets. The analysis in this research is simple regression test, multiple regression test and percentage description. The results showed that the R2 coefficient of the simple regression test in the Hands on Activity experimental class (X1) and the PODE Model (X2) were 55.7% and 64.6%, respectively, and 47.8% in the control class. Multiple linear test results. The results of the joint research have a value of Sig. the value of 0.000 0.005 and the value of Fcount 25.339 Ftable 3.33, it can be concluded that there is an effect of Hands on Activity (X1) and the PODE model (X2) simultaneously there is an effect of understanding the concept (Y1). Analysis of the percentage of class concept understanding there is an increase between the experimental class and the control class. 33 it can be concluded that there is an effect of hands on activity (X1) and the PODE model (X2) simultaneously there is an effect of understanding the concept (Y1). Analysis of the percentage of class concept understanding there is an increase between the experimental class and the control class. 33 it can be concluded that there is an effect of Hands on Activity (X1) and the PODE model (X2) simultaneously there is an effect of understanding the concept (Y1). Analysis of the percentage of class concept understanding there was an increase between the experimental class and the control class